Kelayakan Laboratorium Sebagai Penunjang Pembelajaran Siswa Kompetensi Keahlian Kuliner di SMK Negeri 1 Bangkalan - Rohmatin Alifia Arining; Niken Purwidiani; Sri Handajani; Asrul Bahar (Garina, 2024)
This research aims to describe the feasibility of a laboratory as a support for students' learning in the Culinary Skills Competency program at SMKN 1 Bangkalan with the national education standards prepared by the Ministry of Education and Culture in 2021. From the results of research and calculations for several components, a total average of 87% for the feasibility of facilities and infrastructure stated that the laboratory at SMKN 1 Bangkalan was suitable for supporting learning and 52% for the feasibility of supporting components.